GROWTH AND YIELD OF GREEN BEANS RESPONSE ON GIVING NPK AND RICE HUSK BIOCHAR IN ALLUVIAL SOIL - Mohri, Mohri; Astina, Astina; Surachman, Surachman (Jurnal Sains Pertanian Equator, 2022)
Mung bean (Vigna radiata L) Wilczek) is one of the important legumes or legumes and is widely consumed by the public, especially in Indonesia. Green beans are a source of vegetable protein, vitamins A, B1, C, and E, as well as several other substances that are very beneficial for the human body. Green beans can thrive in loose soil and proper fertilizer application. Rice husk biochar can improve soil physical properties, such as loosening the soil, increasing porosity, aeration, and soil microorganisms, so that roots in the soil can develop properly. NPK fertilizer functions as a supplier of macro nutrients to meet the nutrient needs of plants. This study aims to determine the interaction between NPK and rice husk biochar and to determine the best dose of NPK and rice husk biochar on the growth and yield of green beans in alluvial soil. This research was carried out at a location located in Jl. Sungai Raya Dalam, Pontianak, this research takes place from 22 May 2022 - 11 August 2022. This study used a Completely Randomized Design (CRD) Split Plot namely the effect of NPK fertilizer and rice husk biochar. In this study there are 2 factors, namely Biochar rice husk (b) as the main plot (main plot) as many as 3 treatment levels and NPK 16:16:16 (p) as subplots with 3 treatment levels so that there were 9 treatment combinations with 3 replications, and 5 plant samples. The total number of plants observed was 135 plants. The first factor is the main plot of rice husk biochar (b): b1 = 3 tons/ha, b2 = 5 tons/ha, b3 = 7 tons/ha. The second factor is NPK fertilizer (p): p1 = 400 kg/ha, p2 = 600 kg/ha, p3 = 800 kg/ha. The variables observed were plant height (cm), root volume (cm3), plant dry weight (g), number of pods per plant (fruit), dry seed weight per plant (g), and 100 seed weight (g). Based on the results of the study, it was shown that the effect of NPK and rice husk biochar interacted on the variables of plant height at 4 WAP, number of pods per plant and dry seed weight per plant. The administration of NPK at a dose of 600 kg/ha and rice husk biochar at a dose of 5 tons/ha was the best dose for growth and yield of green beans with an average weight value of fresh pods per plant, which was 36,5 g/plant. Keywords: Alluvial, Green Beans, NPK, Rice Husk Biochar, Response